To solve for x, we need to isolate it on one side of the equation.
First, we can start by adding 5x to both sides to eliminate the -5x term on the left side of the equation:
-5x + 5x + 2 = 67 + 5x
This simplifies to:
2 = 67 + 5x
Next, subtract 67 from both sides to move the constant term to the right side:
2 - 67 = 67 + 5x - 67
This simplifies to:
-65 = 5x
Finally, divide both sides by 5 to solve for x:
-65/5 = 5x/5
This simplifies to:
-13 = x
Therefore, the solution to the equation -5x + 2 = 67 is x = -13.
-5x+2=67 solve x
1 answer